Adherence to a depression self-care intervention among primary care patients with chronic physical conditions: A randomised controlled trial. (November 2016) - McCusker, Jane; Cole, Martin G.; Yaffe, Mark; Strumpf, Erin; Sewitch, Maida; Sussman, Tamara; Ciampi, Antonio; Lavoie, Kim; Belzile, Eric
Objective: Among primary care patients with chronic physical conditions and comorbid depressive symptoms, to assess (1) the effect of lay telephone coaching on adherence to a psycho-educational intervention for depression, (2) demographic characteristics that predict adherence and (3) the association between adherence and 6-month outcomes. Design: Single blind randomised pragmatic trial of a lay telephone-supported depression self-care intervention compared to an unsupported intervention. Methods: All patients received a multimedia toolkit of paper and audiovisual materials on depression that provided education on depression and on self-care for depression. Core tools included a cognitive-behavioural therapy (CBT)-based workbook and a mood monitoring notebook, with opportunities for written exercises and notes, and a video. Intervention group patients were additionally offered telephone coaching. Self-reported use of the materials was assessed at 3 and 6 months post-randomisation; 6-month outcomes were patient satisfaction and change from baseline in depression severity. Results: In all, 223 patients were randomised; 165 (74.0%) completed follow-up. Coached versus uncoached patients reported significantly greater use of the workbook, but not of other tools. Men used more audiovisual tools; women used more paper tools. Self-reported completion of written exercises and a greater number of coach contacts were associated with greater satisfaction, but not with improvement in depression. Conclusion: Telephone coaching can increase adherence to CBT-based tools for depression self-care; however, use of these tools may not improve depression outcomes. Many patients are capable of self-directed use of self-care educational materials. Sex differences in patterns of tool use may be helpful in the targeting of tools.